Impact of digital innovation on the processing of electronic payments and contracting: An overview of legal risks - Phoebus Athanassiou (European Central Bank (ECB), 2017)
Digital innovations in finance have in recent years attracted strong interest from public authorities, financial sector stakeholders and academics alike, inter alia on account of their promise to reduce, or to altogether eliminate, the inefficiencies surrounding the execution and settlement of retail payments, including those linked to remote consumer transactions. For all the promises they hold, and their transformative potential, technological innovations also present challenges, some of which are of a legal nature. With technological innovation still at a formative stage, it is essential to identify and evaluate those challenges, so as to better understand which of their payment-specific applications to encourage (and how), and mitigate the risk of technological innovation destabilising the safety and efficiency of payments. This paper seeks to explore the key legal issues that policy makers may wish to take into account in assessing the merits and risks of digital innovation, with an emphasis on its application to retail payments, and to contribute to an understanding of how technological advances are likely to affect both payment transactions and, no less importantly, the legal relationships between the parties to them. The scope of this paper is limited to an examination of the legal implications of technological innovation for payments associated with consumer transactions, including those entered into online, and settled otherwise than by way of cash. Consequently, this paper will not examine the legal implications of technological innovation for the processing of transactions relating to transferable securities, for financial stability, for the conduct, by central banks, of their monetary policy operations, for the micro-prudential supervision of payment service providers, for competition among established payment service providers and new entrants, and for financial inclusion, issues of great legal and practical significance that merit (and, no doubt, will receive, going forward) specialized attention.
Keywords: K24; 330; FinTech; distributed ledgers; distributed ledger technologies; blockchain; virtual currencies; bitcoin; retail payments; smart contracts